An integrated approach for the measurement of inequality, poverty, and richness - Crespo, N. (2015)
The goal of the paper is to propose a new and integrated approach to the measurement of inequality in income distribution, poverty, and richness. The proposed set of indicators is easy to calculate and is based on a neutral inequality concept. The method allows an objective interpretation of the values for each measure, a decomposition according to households’ characteristics, and an immediate comparison of the results between countries and time periods, thereby offering important conclusions for policy action. We illustrate the application of the measures with data from Portugal, finding that: (i) 17.78% of the individuals belong to households classified as poor while 7.03% are rich and 75.19% are classified as middle class; (ii) it is necessary to redistribute 23.78% of the total income of the economy to obtain perfect equality; (iii) 2.09% of the total income in the economy is enough to eradicate poverty.